2017
DOI: 10.1051/epjconf/201714302127
|View full text |Cite
|
Sign up to set email alerts
|

Experimental research of flow servo-valve

Abstract: Abstract. Positional control of pneumatic drives is particularly important in pneumatic systems. Some methods of positioning pneumatic cylinders for changeover and tracking control are known. Choking method is the most development-oriented and has the greatest potential. An optimal and effective method, particularly when applied to pneumatic drives, has been searched for a long time. Sophisticated control systems with algorithms utilizing artificial intelligence methods are designed therefor. In order to desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…To control the pair of muscles, a part of the pressure characteristics of the valve, shown in Figure 5, was used. Accurate author's research presented in the works [14,15] showed asymmetry in the valve operation, leakage and non-linearity.…”
Section: Test Standmentioning
confidence: 99%
“…To control the pair of muscles, a part of the pressure characteristics of the valve, shown in Figure 5, was used. Accurate author's research presented in the works [14,15] showed asymmetry in the valve operation, leakage and non-linearity.…”
Section: Test Standmentioning
confidence: 99%
“…Pneumatic systems are currently the most ecological and economical media for industry, but they are used in less demanding processes. The complexity of designs and multiplicity of applications of pneumatic systems results mainly from the advantages of compressed air, which enables the generation of significant forces, and from a large assortment of valves [ 19 , 20 , 21 ] and pneumatic components. In industry, pneumatic installations for the distribution of compressed air are commonly made of PP-R polypropylene or PP-R polypropylene with an external aluminum layer and on fasteners, connected by welding with a temperature resistance up to 60 °C and a maximum pressure of 20 bar.…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al [17] contributed to cavitation theory by studying the collapse of two cavitation bubbles with a high‐speed camera. Experiments by Takosoglu et al [18] on a servo valve provided a good experimental reference. Yan et al [19] provided good theoretical guidance for designing a servo valve by studying its nozzle jet mechanism.…”
Section: Introductionmentioning
confidence: 99%